PENERAPAN PASAL 18 UNDANG-UNDANG NOMOR 20 TAHUN 2001 TERKAIT DENGAN UANG PENGGANTI GUNA PENGEMBALIAN KERUGIAN KEUANGAN NEGARA - Toman Epy Lazarus Ramandey; Faisal Malik; Nam Rumkel (The Juris, 2020)
This paper will specifically analyze the application of Article 18 of Law Number 20 Year 2001 concerning the Eradication of Corruption as compensation for recovering state financial losses at the Jayapura District Prosecutor's Office. This type of research is normative or doctrinal law research. The legal materials used are primary legal materials, namely legal regulations and secondary legal materials consisting of statistical data from the Jayapura District Prosecutor's Office, and the Corruption Court at the Jayapura Class I A District Court, text books, legal journals, comments - Comment and legal dictionaries. Data collection was carried out through document study and literature study. The collected data were then analyzed qualitatively. The results of the study show that the return of a number of funds or payment of replacement money equal to the value of corruption committed by perpetrators of corruption for the return of state losses does not eliminate criminal charges as stated in Article 4 of Law Number 20 Year 2001 concerning amendments to Law Number 31 Year 1999 concerning the Eradication of Corruption Crime. The rules regarding the mechanism for paying replacement money to recover state losses due to corruption are very clear. Namely, based on the Attorney General's decision Number: Kep-518/J.A/11/2001 dated November 1, 2001 concerning the Mechanism of Payment of Replacement Money.